State-Owned Enterprises’ Stock Market Reaction to Danantara Inauguration: An Event Study Analysis - Maulidah Fitria; Abrori, Rian (International Economic Conference of Business and Accounting, 2025)
Danantara (Daya Anagata Nusantara) is a strategic initiative of the Indonesian government that has generated various reactions among the public and capital market. Public concerns and distrust were reflected in massive withdrawals from state-owned banks and the decline in state-owned bank stock prices. Nevertheless, empirical findings have not yet captured this reaction. This study aims to analyze the market reaction to the inauguration of Danantara by examining the differences in abnormal return and trading volume activity (TVA) of state-owned enterprises (SOEs). We use data of 22 SOEs listed on the Indonesia Stock Exchange. It were analyzed using an event study approach with paired sample t-tests to compare the average abnormal return and TVA before and after the event. The event window was set for 21 days, including 10 days before, 1 event day, and 10 days after the inauguration. The results indicate that, in aggregate, there were no significant differences in the average abnormal return and before and after the initiation of Danantara. However, a notable finding emerged from sectoral analysis: state-owned banks experienced a sharper decline in abnormal return and TVA compared to SOEs in other sectors. This suggests that negative public reactions, as reflected in withdrawals from state-owned banks, were also captured in the capital market, although the effect was not strong enough to influence the overall test results. This study provides insights into the sensitivity of the banking sector to public sentiment, which is an important consideration for the government when designing similar initiatives in the future.